Performance modeling: A system-based approach to exercise selection - Read, P. J.; Bishop, C.; Brazier, J.; Turner, A. N. (Strength and Conditioning Journal, 2016)
In the process of designing programs for athletes, often strength and conditioning coaches do not develop an appropriate system which is integrated with the achievement of specified performance goals. The system of performance modeling promotes the design of training programs which use a clear system of analysis, testing, and exercise prescription, which increases transfer of training and enhances sports performance. This article outlines the concept of performance modeling using a sport example. Further considerations to promote individualization of training prescription using a progression/regression sequence are also suggested.